Toward an Integrated Framework of Business Education and Training Innovation for Digital Workforce Readiness: A Systematic Review Across Finance, Marketing, HRM, and Strategic Management - Dedi Supiyadi; Neti Budiwati; Ahmad Rasyiddin; Gilang Bhirawa; Bambang Triputranto; Khaerudin Sidik Patoni (Sinergi International Journal of Management and Business, 2026)
Digital transformation is reshaping business organisations at a pace that consistently outstrips workforce competency, rendering business education and training innovation a strategic imperative. This study synthesises empirical evidence on business education and training innovation for digital workforce readiness across four business functions: finance, marketing, HRM, and strategic management. Following the PRISMA 2020 protocol, a Scopus search (English-language records, 2015–2026) yielded 108 documents; after two-stage screening and quality assessment (MMAT 2018), a final corpus of 63 articles was obtained (mean score: 3.92/5.00). Narrative synthesis and thematic analysis were applied. Three phases characterise the literature: emergence (2020–2021), consolidation (2022–2023), and acceleration (2024–2026), with emerging markets accounting for 54% of research contexts overall, of which Indonesia, India, Malaysia, and Thailand together contribute 49% of the corpus. Seven innovation typologies were identified, distributed asymmetrically: Strategic Management (76.2%) and HRM (52.4%) dominate, while Finance (11.1%) and Marketing (3.2%) remain markedly underrepresented. No article integrates all four functions simultaneously, corroborating the study's motivating research gap within the scope of the Scopus corpus searched. Organisational learning emerges as the most consistently supported mediating mechanism, validated by seven SEM studies in the pathway from training innovation to organisational performance, with digital leadership and digital maturity as the primary enabler and moderator. Limited to Scopus and English-language articles, this study proposes a preliminary integrated framework as its theoretical contribution.